In search of a Godless spirituality - García Mourelo, Santiago (Razón y fe, 2019)
One of the new forms of religiosity in westernized societies is the socalled “Godless spirituality”. From an attitude of dialogue, this article wants to show its main elements drawing from the writings of A. Compte-Sponville and F. Mayorga. Despite its alleged emancipation from religions, “Godless spirituality” receives its fundamental presuppositions and aspirations, such as the “oceanic feeling”, of advaita vedanta neo-Hinduism. This is a trait that raises philosophical and theological questions. The immanent spirituality, centered exclusively on the individual and his possibilities, rejects all otherness of divine order, an issue that, despite being a confrontation with the Christian faith, is also present within the Church in different ways. Therefore, the ecclesial community must undertake or resume some ways to respond to this situation.
Keywords: Spirituality; atheism; oceanic feeling; secularization; Feliciano Mayorga; André Comte-Sponville